Halal Research During Covid-19 Pandemic: A Bibliometric Analysis - Anita Priantina; Safeza Mohd Sapian; Melvina Syahnum (Faculty of Islamic Economics and Business | Institut Agama Islam Negeri Palangka Raya, 2024)
Non-Indexed Publication